PENGARUH METODE PEMBIASAAN TERHADAP PEMBENTUKAN SIKAP TANGGUNG JAWAB ANAK USIA 4-5 TAHUN (Penelitian Ex-post Facto di KB-TKIT Raudhatul Jannah Cilegon Banten) - Jamilatus Surifah; Laily Rosidah; Fahmi Fahmi (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2018)
This study aims to examine and obtain data empirically about the influence of methods of habituation to the formation of responsibility attitude of children aged 4-5 years. This research was conducted in KB-TKIT Raudhatul Jannah Cilegon-Banten in January-May 2018. The method used in this research is quantitative research with Ex-post Facto research design. The population in this study were 84 pairs of X and Y. The sample used was 69 pairs of X and Y. The data was collected using questionnaire instrument and observation instrument. The questionnaire instrument is used to measure the variable of habituation method and the variable forming of responsibility attitude of the child. And supported by the observation instrument to measure the variable formation of responsibility attitude. The data were analyzed using Kolmogorov Smirnov normality test, simple linear regression test using regression coefficient, determination coefficient and hypothesis test. Based on the results of normality calculations on both variables are variable methods of habituation and variable formation of responsibility attitude of children obtained results of 0.200 > 0.05, it can be concluded that the two data variables in this study normal distribution. Result of calculation of simple linear regression obtained v = 2,753 + 0,948X, hence can be concluded that variable of method of habituation have positive influence to forming of responsibility attitude of child and based on coefficient of determination value that method of habituation give influence equal to 86,6% to formation of child responsibility attitude. Hypothesis testing is done by t test with result t count 20,852 > t table 1,996. Thus it can be concluded that there is influence of methods of habituation to the formation of responsibility attitude of children aged 4-5 years.